Pengurangan Resiko Bencana Berbasis Komunitas Melalui Pembentukan Desa Tangguh Bencana di Kabupaten Pidie Jaya Nanggroe Aceh Darussalam - Muzakir Zainal; Marwan Marwan; Muhammad Yanis; Muksin Muksin (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
Aceh province is traversed by the Sumatran fault which stretches for 1900 km from the southern tip of Sumatra Island to the Andaman Sea. Seismic activity along this active fault line poses a serious threat to Aceh including in Pidie Jaya Regency. This community assistanc formulated a program called Desa Tangguh Bencana (DESTANA) to optimize the active role of the community by evaluating Participatory Rural Appraisal (PRA). The target was rural communities with diverse educational and economic backgrounds. The activity was carried out by: providing information on disaster awareness, providing assistance to village governments to formulate village regulations based on disaster risk agreements, and map making and installation of information boards for evacuation routes and path planning by considering local values ​​in the village. The program resulted in the formation of a disaster risk team and a community group who were alert to ongoing disasters, as well as an increase the community’s knowledge.